TAHLIL AL- AKHTO’ FII KITABATIL LUGGHOTIL AROBIYYAH FII TA’LIMIL IMLA’ BIMADROSATI DARUT TAUHID ZAINUL HASAN GENGGONG - Hidayati, Syamsi; Yunus, Moch; Zainullah, Zainullah (Universitas Islam Negeri Mataram, 2024)
Writing is one of the four skills in Arabic language acquisition. Improving writingproficiency can be achieved through spelling instruction. Dictation, an exercisecommonly used in Arabic instruction, involves the teacher reciting a text or passage,and the student transcribing it. This study aims to delineate the fundamental types ofwriting errors among first-grade students in a religious school. Employing a qualitativedescriptive research approach, the study utilizes error analysis as its methodologicalframework. Multiple data collection methods, including tests, observations, interviews,and documentation, were employed by the researcher. The results of this study showthat the errors identified in this study encompass mistakes in writing hamza, hamzaomission, letter deletion, letter addition, as well as errors in letter substitution and thewriting of taa. The primary factors contributing to these errors include students'unfamiliarity with correct writing forms, inadequate Arabic writing practice, anddeficiencies in grammar and morphology skills.